1969
DOI: 10.1136/jcp.22.2.199
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation factors in chronic liver disease

Abstract: Coagulation studies were carried out on 30 patients with chronic liver disease. The clotting defect was complex and involved factors V, VII, IX (Christmas factor), and prothrombin. Some patients showed a significant depression of factor IX in the presence of a normal one-stage prothrombin time. Thrombotest was found to be a good indicator of factor IX deficiency in this group of patients and may be of use as an additional liver function test. The screening of patients with liver disease for surgery or liver bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
14
0
1

Year Published

1972
1972
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 13 publications
(8 reference statements)
3
14
0
1
Order By: Relevance
“…Cirrhotic patients with features of hepatic decompensation had a significantly lower mean level of activity (40 %) than the 'contrast' patients with surgical obstruction of the major bile ducts (93 %). Patients with chronic active liver disease had moderate depression of factor VII levels and those with non-cirrhotic alcoholic liver damage had mean activities similar to the contrast group.Factor VII levels could not be correlated with BSP retention but there was a correlation with serum albumin concentration.It is concluded that the prothrombin time using the Quick test with a standardized thromboplastin showing good sensitivity to factor VII, eg, the Manchester reagent (BCT), provides a reliable index of coagulability in chronic liver disease, and specific factor VII assays are not indicated.The liver is the major site of synthesis of many clotting factors (Roberts and Cederbaum, 1972) and it is not unexpected that reduced levels of these have been reported in liver disease (Owren, 1949;Hallen and Nilsson, 1964;Donaldson et al, 1969).Biochemical tests of liver function have traditionally been used to assess and monitor the progress of patients with hepatic disorders. More recently, both broad-spectrum tests of blood clotting, ie, onestage prothrombin time and partial thromboplastin time and specific clotting factor measurements, particularly factor VII assays (Dymock et al, 1975), have proved of additional value in the diagnosis and assessment of liver disease.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cirrhotic patients with features of hepatic decompensation had a significantly lower mean level of activity (40 %) than the 'contrast' patients with surgical obstruction of the major bile ducts (93 %). Patients with chronic active liver disease had moderate depression of factor VII levels and those with non-cirrhotic alcoholic liver damage had mean activities similar to the contrast group.Factor VII levels could not be correlated with BSP retention but there was a correlation with serum albumin concentration.It is concluded that the prothrombin time using the Quick test with a standardized thromboplastin showing good sensitivity to factor VII, eg, the Manchester reagent (BCT), provides a reliable index of coagulability in chronic liver disease, and specific factor VII assays are not indicated.The liver is the major site of synthesis of many clotting factors (Roberts and Cederbaum, 1972) and it is not unexpected that reduced levels of these have been reported in liver disease (Owren, 1949;Hallen and Nilsson, 1964;Donaldson et al, 1969).Biochemical tests of liver function have traditionally been used to assess and monitor the progress of patients with hepatic disorders. More recently, both broad-spectrum tests of blood clotting, ie, onestage prothrombin time and partial thromboplastin time and specific clotting factor measurements, particularly factor VII assays (Dymock et al, 1975), have proved of additional value in the diagnosis and assessment of liver disease.…”
mentioning
confidence: 99%
“…The liver is the major site of synthesis of many clotting factors (Roberts and Cederbaum, 1972) and it is not unexpected that reduced levels of these have been reported in liver disease (Owren, 1949;Hallen and Nilsson, 1964;Donaldson et al, 1969).…”
mentioning
confidence: 99%
“…Of particular concern are warfarin users with heart failure (HF) who subsequently suffer from hepatic dysfunction and are at increased risk of hemorrhage. [15][16][17] Gurwitz et al found that hemorrhage is the most common type of preventable adverse drug event among older persons in an ambulatory clinical setting. 18 Landefeld and Beyth found that the average annual frequencies of fatal, major, and major or minor bleeding during warfarin therapy were 0.6%, 3.0%, and 9.6%, respectively.…”
mentioning
confidence: 99%
“…Los factores V y VIII son los primeros en disminuir por poseer las vidas medias más cortas (12 y 4-6 horas, respectivamente) (38). Es común que los pacientes cirróticos sufran reducciones moderadas del factor VII, identificándose una relación significativa entre los niveles de factor VII y el tiempo de protrombina (TP) (r = 0,76, p <0,001) (39). Cuando se evalúan las pruebas de coagulación en pacientes con hepatopatías, es importante descartar defectos congénitos; el más frecuente es la deficiencia de factor VII (1 caso por cada 500 000 nacimientos) (40).…”
Section: Alteraciones En La Hemostasia Secundariaunclassified